Acute bacterial prostatitis after transrectal ultrasound‐guided prostate biopsy: Epidemiological, bacteria and treatment patterns from a 4‐year prospective study. (1st August 2013) - Campeggi, Alexandre; Ouzaid, Idir; Xylinas, Evanguelos; Lesprit, Philippe; Hoznek, Andras; Vordos, Dimitri; Abbou, Claude‐Clément; Salomon, Laurent; de la, Alexandre
<x xml:space="preserve">Abstract</x> Objectives To evaluate the incidence, and clinical and bacterial features of iatrogenic prostatitis within 1 month after transrectal ultrasound‐guided biopsy for detection of prostate cancer. Methods From January 2006 to December 2009, 3000 patients underwent a 21‐core transrectal ultrasound‐guided prostate biopsy at Henri Mondor Hospital (Créteil, France) and were prospectively followed. All patients had a fluoroquinolone antimicrobial prophylaxis for 7 days. The primary study end‐point was to evaluate the incidence of iatrogenic acute prostatitis within 1 month after the biopsy. The secondary end‐point was to analyze the clinical and the bacterial features of the prostatitis. Results Overall, 20 patients of the entire study population (0.67%) had an acute bacterial prostatitis within 2.90 ± 1.77 days (range 1–7 days) after the transrectal ultrasound‐guided biopsy. The groups of patients with (n = 20) and without (n = 2980) infection were similar in terms of age, prostate‐specific antigen level and prostate volume. Escherichia coli was the only isolated bacteria. The subsequent tests for antibiotic susceptibility showed a 95% resistance for fluroquinolone and amoxicillin. Resistance to amoxiclav, trimethoprim‐sulfamethoxazole, third generation cephalosporin and amikacin was 70%, 70%, 25% and 5% respectively. No resistance to imipenem was reported. They were all admitted for treatment without the need of intensive care unit referral. Complete recovery was achieved after 21.4 ± 7 days of antibiotic treatment. Conclusions A fluroquinolone‐based regimen still represents an appropriate prophylaxis protocol to minimize the risk of acute prostatitis secondary to prostate biopsy. Patients should be provided the appropriate care soon after the onset of the symptoms. An intravenous third generation cephalosporin or imipenem‐based therapy seem to provide satisfying results.